Glyptothorax heokheei, a new species of catfish (Teleostei: Sisoridae) from the Brahmaputra River drainage, Arunachal Pradesh, Northeast India - Singh, Pratima; Chowdhury, Basudhara Roy; Gurumayum, Shantabala Devi; Kosygin, Laishram (Zootaxa, 2023)
Glyptothorax heokheei, a new species of sisorid catfish is described from the Brahmaputra River drainage in India. It can be distinguished from all congeners, except G. dikrongensis, G. indicus, G. rugimentum and G. obliquimaculatus, in having the unculiferous striae of thoracic adhesive apparatus extending anteriorly onto gular region. Glyptothorax heokheei is distinguished from G. dikrongensis and G. obliquimaculatus in having a slender body at the anus, more serrations on posterior margin of pectoral-fin spine, greater number of branched anal fin rays, and the extremity of dorsoposterior margin of adipose fin uniformly convex (vs. sharply angular). It differs from G. rugimentum in having a chevron-shaped (vs. rhomboidal) thoracic adhesive apparatus, more serrations on posterior margin of pectoral-fin spine, and lacking vertical bars on body. Glyptothorax heokheei differs from G. indicus in having a shorter post-adipose distance, smaller interorbital width, more serrations on posterior margin of pectoral-fin spine and nasal barbel not reaching (vs. reaching) anterior margin of eye. Glyptothorax heokheei is the fifth species of the genus possessing unculiferous ridges of thoracic adhesive apparatus extending anteriorly onto the gular region.